Improving performance : how to manage the white space on the organization chart - Rummler, Geary A.; Brache, Alan P., 1950- (San Francisco, CA : Jossey-Bass, 1995)
This book offers an integrated framework for achieving competitive advantage by managing organizations, processes, and jobs effectively.
Includes bibliographical references (p. 219-221) and index.
oif 16/10/14
Loan
Keywords: Industrial productivity; Performance; Organizational effectiveness